EXPERT SYSTEM DIAGNOSIS PENYAKIT JANTUNG MENGGUNAKAN METODE RULE-BASED REASONING BERBASIS ANDROID - Agif Hafizhan; Fauzi, Rahmat (Computer Science and Industrial Engineering, 2025)
Cardiovascular disease remains one of the leading causes of mortality worldwide, emphasizing the urgency of early detection and preventive efforts. This study presents the design and development of an expert system application for the diagnosis of heart disease using a Rule-Based Reasoning method, implemented on an Android platform. The application enables users to input symptoms and severity levels through an intuitive interface. These inputs are then matched against a knowledge base consisting of expert-defined rules to generate potential diagnostic results. The system is expected to support both individuals and healthcare workers by providing preliminary insights before further medical examination. The use of mobile technology ensures wider accessibility, real-time interaction, and ease of use. Testing results demonstrate that the application performs with satisfactory accuracy in diagnosing based on symptom patterns. Future enhancements may include integration with Certainty Factor methods or machine learning to improve diagnostic precision.